Research of the Finite Element Multi Tooth Contact of Spiral Bevel Gear with Different Load - Chen Zhiliang; Yang Rongsong; Liu Qiang (Jixie chuandong)
According to the mathematical model of milling tooth processing of spiral bevel gear,the tooth surface parameters of spiral bevel gear are obtained.The precise three- dimensional model is established.By using the ANSYS workbench software,the change rule of contact stress of spiral bevel gear with different load under multi tooth meshing state is analyzed.The more accurate contact stress of spiral bevel gear is obtained.The theoretical basis for gear fatigue life calculation is provided.